The phenomenon of historical reenactment in the XX-XXI centuries culture - A. A. Solovei; A. M. Tormakhova (Ukrainian Cultural Studies, 2020)
The article deals with the phenomenon of historical reenactment. It is noted that its actualization in the context of the culture of the XX–XXI centuries is due to a change in trends in the development of society. The formation of a visual turn contributes to the emphasis on forms of perception that are focused on interactivity. The "dry" story of past events is extremely difficult to perceive in the context of the spread of digital culture. Mankind is accustomed to the appearance of events that shock, impress, inspire and most of the impact is due to visual stimuli. There are several types of historical reconstruction – "living history" and tournaments. The movement of historical reconstruction in Europe can be divided into historical reenactment, which is divided into "living history" and combat reenactment, as well as creative reconstruction. Instead, in the Ukrainian space more attention is paid to the development of historical reconstruction in the dimension of sports competitions – ISB (historical medieval battles). Reproduction of elements of everyday life can act as a valuable source of information about culture. The spread of the phenomenon of historical reconstruction had an extremely great potential for the socio-cultural sphere. Historical reconstruction can serve as a tool for modifying museum practices. In recent years, there has been a steady trend towards the appearance of theatrical performances that revitalize the work of museum institutions. The actualization of historical reconstruction leads to the formation of festivals associated with historical battles. Often the festival of historical reconstruction includes various competitions and contests – fencing, archery or crossbow shooting, mass battles, a competition for the most authentic uniform. They draw attention to military affairs and history, combining integrative, cognitive functions, as well as being a part of leisure. The results of the study can be practically applied in the field of cultural management, project activities and in the work with the preservation of cultural heritage – material and spiritual.